53.7k views
5 votes
Simplify completely 2x2+13x+20/x2-5x-36

1 Answer

4 votes

For this case we must factor.

Numerator:


2x ^ 2 + 13x + 20

We must change the term of the medium by the sum of two numbers that when multiplied give as result
(2) (20) = 40, and when summed give as result +13.

These numbers are: 5 and 8


(5) (8) = 40\\5 + 8 = 13

So:


2x ^ 2 + 8x + 5x + 20

We take common factor on both sides:


2x (x + 4) +5 (x + 4)\\(2x + 5) (x + 4)

So,
2x ^ 2 + 13x + 20 = (2x + 5) (x + 4)

Denominator:


x ^ 2-5x-36

We should look for two numbers that multiplied give -36 and added as a result -5.

-9 and +4

Thus,
x ^ 2-5x-36 = (x-9) (x + 4)

Then,
\frac {2x ^ 2 + 13x + 20} {x ^ 2-5x-36} =


\frac {(2x + 5) (x + 4)} {(x-9) (x + 4)} =\\\frac {(2x + 5)} {(x-9)} =

Answer:


\frac {(2x + 5)} {(x-9)}


User ArtemSky
by
5.9k points